2022
DOI: 10.3390/nano12172933
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Chitosan–Polyvinyl Alcohol Nanofiber Dressings Loaded with Bioactive Ursolic Acid Promoting Diabetic Wound Healing

Abstract: The design and development of novel dressing materials are urgently required for the treatment of chronic wounds caused by diabetic ulcers in clinics. In this study, ursolic acid (UA) extracted from Chinese herbal plants was encapsulated into electrospun nanofibers made from a blend of chitosan (CS) and polyvinyl alcohol (PVA) to generate innovative CS-PVA-UA dressings for diabetic wound treatment. The as-prepared CS-PVA-UA nanofiber mats exhibited randomly aligned fiber morphology with the mean fiber diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Moreover, it possesses anti-inflammatory properties by suppressing M1 and stimulating M2 phenotype of macrophages, inhibiting TNF-α and IL-6 expression, and reducing ROS production. The in vivo study revealed an improved closure rate and enhanced revascularization and re-epithelization [ 119 ].…”
Section: Skinmentioning
confidence: 99%
“…Moreover, it possesses anti-inflammatory properties by suppressing M1 and stimulating M2 phenotype of macrophages, inhibiting TNF-α and IL-6 expression, and reducing ROS production. The in vivo study revealed an improved closure rate and enhanced revascularization and re-epithelization [ 119 ].…”
Section: Skinmentioning
confidence: 99%
“…Because they have many desirable properties for skin wound healing, nanofibrous composites have received significant attention in the past few decades [ 97 , 98 , 99 , 100 , 101 ]. Nanofibers can be designed to possess a random or aligned structure, and the fiber diameter can be adjusted to closely match that of collagen fibrils in the natural skin ECM (i.e., the range of 100–200 nm).…”
Section: Different Types Of Bioactive Wound Dressings To Modulate Mac...mentioning
confidence: 99%
“…The UA-loaded nanofibers significantly reduced the M1 phenotypic polarization of macrophages and effectively restored the M2 polarization in vitro. In a diabetic wound model, this scaffold was found to improve wound closure, re-epithelialization, revascularization, and hair follicle regeneration [ 99 ]. Similarly, anemoside B4, an anti-inflammatory ingredient of the Chinese medicine Pulsatilla , has been loaded into an electrospun nanofibrous wound dressing, which significantly suppressed the lipopolysaccharide-stimulated differentiation of pro-inflammatory macrophages in vitro and accelerated diabetic wound healing in vivo [ 103 ].…”
Section: Different Types Of Bioactive Wound Dressings To Modulate Mac...mentioning
confidence: 99%
“…Briefly, slow rate of ulcer healing leads to microbial infection, gangrene, and trauma. Infected foot ulcer usually leads to hospitalization and ends up with amputation 2 – 4 . Delayed healing in diabetic patients is attributed to complicated pathological features that retard the healing process 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Although wound closure occurs naturally, it is extremely complicated in diabetic patients as there is no well-defined followed protocol till now for the complete healing of diabetic wounds and ulcers 2 , 15 .…”
Section: Introductionmentioning
confidence: 99%